Biomarkers for Chimeric Antigen Receptor T Cell Therapy in Acute Lymphoblastic Leukemia: Prospects for Personalized Management and Prognostic Prediction - Hong, Ruimin; Hu, Yongxian; Huang, He (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) T cell therapy represents a breakthrough in immunotherapy with the potential of ushering in a new era in cancer treatment. Remarkable therapeutic response and complete remission of this innovative management have been observed in patients with relapse/refractory acute lymphoblastic leukemia. With CAR-T cell therapy becoming widely used both in multicenter clinical trials and as a commercial treatment, therapeutic efficacy monitoring and management of toxicities will be indispensable for ensuring safety and improving overall survival. Biomarkers can act not only as effective indicators reflecting patients’ baseline characteristics, CAR-T cell potency and the immune microenvironment, but can also assess side effects during treatment. In this review, we will elaborate on a series of biomarkers associated with therapeutic response as well as treatment-related toxicities, and present their current condition and latent value with respect to the clinical utility. The combination of biomarker research and CAR-T cell therapy will contribute to establishing a safer and more powerful monitoring system and prolonging the event-free survival of patients.